THE PERFORMANCE EFFICIENCY OF THE PERSONNEL AT THE OFFICE OF THE PRIVATE EDUCATION COMMISSION - จิตรมหรรณพ ลัธธนันต์ (Journal of MCU Phetchaburi Review, 2025)
This research aims to 1) study the performance of personnel at the Office of the Private Education Commission (OPEC) and 2) compare the performance of personnel at the OPEC by individual factors, including gender, age, education level, average monthly income, and length of employment. This research is a quantitative study. The sample consisted of 165 civil servants, government employees, and contract employees working at the OPEC. Multi-stage sampling was used, including stratified random sampling, quota random sampling, and simple random sampling. Data were collected using a questionnaire. Reliability was analyzed using Cronbach’s Alpha Coefficient. The reliability of the entire questionnaire was .97. The research statistics used included descriptive statistics, including percentages, means, and standard deviations, and inferential statistics, including t-tests and one-way ANOVAs. The results revealed that 1) the overall performance efficiency of the Office of the Private Education Commission personnel was at a high level. 2) The performance efficiency of the Office of the Private Education Commission personnel with different genders, ages, education levels, average monthly income, and length of employment did not differ significantly.